A Mathematical Index Model Analysis Of Working Capital Management Efficiency In The Indian Private Healthcare Sector (Journal of Pharmaceutical Negative Results, 2022)
A hallmark of standard business management is the capability to maintain a strong balance between profitability, growth and liquidity by efficiently utilizing the working capital of the company. This study is an attempt to view the strategic perspective of working capital management policy and practices with respect to efficiency as well as profitability of Indian healthcare sectors. The newness of this study is, it did not use the conventional ratio analysis methods for its analysis, rather used mathematical index-based formula as well as regression to analyze the efficiency of working capital management and their causal relationships. Financial data of 30 companies listed in Bombay stock exchange (BSE) of India, were collected for the period of ‘2019’ to ‘2022’ for this study. Findings suggest that due to Covid -19, it has become challenging for private healthcare providers to maintain the financial health of the healthcare sectors due to over burdens of capacity building for Covid patients in hospitals. In this study period some companies were found less efficient in managing their working capital properly due to the reason the healthcare sector belongs to the service industry and efficient working capital management is a very challenging task for the company. It was suggested that finance managers or policy makers by increasing the utilization index be able to reduce the operating cycle of the company. Several researches were conducted on working capital management in the Indian manufacturing industry using conventional ratio analysis, but very few studies were done using this methodology during Covid -19 period in the private healthcare sector of India which belongs to the service industry. This study will be helpful for policy makers and practitioners of working capital management in various industries. This will give a scope to the future researchers for further study of working capital management practices in both manufacturing and service sectors.